Low concentration thermoresponsive hydrogels from readily accessible triblock copolymers. Issue 20 (29th April 2016) - Despax, Laurie; Fitremann, Juliette; Destarac, Mathias; Harrisson, Simon
Abstract : Dilute (<1 wt%) aqueous solutions of ultrahigh molecular weight triblock copolymers (with M n up to 500 000 g mol −1 ) comprising a long central hydrophilic block of polydimethylacrylamide and shorter terminal blocks of poly( N -isopropylacrylamide) form gels on heating. Abstract : Dilute (<1 wt%) aqueous solutions of ultrahigh molecular weight triblock copolymers (with M n up to 500 000 g mol −1 ) comprising a long central hydrophilic block of polydimethylacrylamide and shorter terminal blocks of poly( N -isopropylacrylamide) form gels on heating. The incorporation of a charged monomer, 2-acrylamido-2-methylpropanesulfonic acid, into the central block leads to significant improvements in mechanical properties and formation of a crosslinked network at concentrations as low as 0.05 wt%. All monomers and transfer agents used in the study are available on an industrial scale.